RODRÍGUEZ VALLS, Francisco, ¿Qué es la antropología?, Sevilla, Senderos, 2020 - Martín Navarro, Alejandro (Contrastes. Revista Internacional de Filosofía, 2021)
Reseña RODRÍGUEZ VALLS, Francisco, ¿Qué es la antropología?, Sevilla, Senderos, 2020